ANALISIS KEPATUHAN MUSLIM INDONESIA DALAM PRAKTIK KEWARISAN ISLAM (Studi Relasi Ayat Waris dengan Hadits Punahnya Ilmu Kewarisan) - Wasman Wasman; Afif Muamar (UIN Siber Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to find out the current implementation of Islamic inheritance law in Indonesia and how to provide an understanding of the division of inheritance in Indonesia. This study is classified as normative research using qualitative methods, which is classified as a type of literature review. The results of this study, namely first, the practice of dividing inheritance among Muslim communities in Indonesia has not been fully implemented. This happened due to the influence of two causal factors, including (1) European historical factors which divided its population into three groups, namely people and those who were equated with Europeans. Foreign Easterners (Chinese), and other Foreign Easterners and Indonesians who focus on European law. (2) Social Factors. Disobedience of some of the Indonesian Muslim community to study Islamic inheritance (faraidh). And second, there is a need for a movement to socialize the science of inheritance on an ongoing basis in terms of education, Islamic study organizations, and religious organizations.Â Keywords: Islamic Society; Inheritance Law; and The Era of Globalization